Executive dysfunction in idiopathic epilepsy: the journey so far - Koganti, Haritha; Colaco, Vimala; Sundaramurthy, Harsha; Paneyala, Shasthara; C., Nemichandra S. (International Journal of Research in Medical Sciences, 2020)
Epilepsy is one of the most common neurological disorders known to man with a high global prevalence. This disease process affects the overall quality of life. In recent times the concept of executive dysfunction in patients with epilepsy has emerged. This phenomenon has widespread therapeutic implications. This review hence aims to summarize our current understanding of the topic, highlighting the results of benchmark studies and outlining the aspects that require further research. The keywords epilepsy, executive dysfunction and cognitive retraining were used in the search engines of Pubmed and Google scholar and articles identified were extensively reviewed. The consensus of this review is that executive dysfunction is a phenomenon that occurs in patients with epilepsy irrespective of epilepsy type, however the magnitude varies with contributory factors which include poor seizure control. Furthermore, patients with cognitive dysfunction have a further decline over the course of the disease process, however longitudinal studies in regard to the same are lacking and there is a need for additional research in this regard.